A trajetória das agriculturas e das sementes: caminhos e objetivos distintos - Medeiros, Rita de Cássia Araújo de (Universidade Federal Rural do Semi-Árido, 2017)
From the beginning of agriculture to the present day, the way in which the human being has been related to the environment has caused profound changes in the environment. Giving a historical leap, a deeper modification in the relationship between human nature and what became known as the modernization of agriculture through the assumptions of the green revolution from the second half of the last century. Parallel to this change remains and a question arises to this "modernized model" initially called alternative agriculture and that today is within the perspective of agroecology. Therefore, based on a literature review and some experiments on the conservation of seeds, we seek to analyze the conflicting evolution of modern agriculture and its counterpoint that is agroecology, taking as protagonist of this process the seed, both from the standpoint of industrial agriculture referenced through transgenic seeds, and of agroecology through non-artificialized seeds. Being of critical importance to reflect critically on the trajectory of the agricultural and the seeds throughout the history of the humanity, with emphasis to the impasses in the production of quality foods in the contemporary society
Monografia
Keywords: Agriculturas alternativas; Agroecologia; Agronegócio; Sementes tradicionais; Modernização; Alternative agricultural crops; Agroecology; Agribusiness; Seeds; Modernization of Agriculture; CIENCIAS AGRARIAS::AGRONOMIA